Acute lymphoblastic leukemia with low hypodiploid/near triploid karyotype is a specific clinical entity and exhibits a very high TP53 mutation frequency of 93%. Issue 6 (11th March 2014) - Mühlbacher, Verena; Zenger, Melanie; Schnittger, Susanne; Weissmann, Sandra; Kunze, Franziska; Kohlmann, Alexander; Bellos, Frauke; Kern, Wolfgang; Haferlach, Torsten; Haferlach, Claudia
<x xml:space="preserve">Abstract</x> B lymphoblastic leukemia/lymphoma (ALL) are subdivided by the WHO classification into five subgroups defined by specific translocations and two further subgroups defined by the number of chromosomes. The hypodiploid subgroup is heterogeneous and comprises ALL with a chromosome number of <46. To characterize a specific subset with low hypodiploid karyotype, we performed chromosome banding analysis, FISH, array comparative genomic hybridization, and mutational analyses of FBXW7, NOTCH1, KRAS, NRAS, TP53, and IKZF1 in 29 cases. We observed a nonrandom pattern of chromosome losses, including chromosomes 3, 7, 13, 15, 16, and 17. A deletion encompassing the CDKN2A/B locus was the only recurrent structural abnormality. A duplication of the low hypodiploid karyotype occurred frequently, resulting in a near triploid karyotype based on the definition by merely counting chromosomes but in fact was a very low tetraploid chromosome set. Mutational analyses revealed no mutations in IKZF1, FBXW7, NOTCH1, and KRAS and only one mutation in NRAS. However, we discovered a high frequency of TP53 mutations in 93% (27/29) of cases. In 26/27 cases with TP53 mutation, the second TP53 allele was lost due to monosomy 17. Median overall survival was short (18.5 months), which might be related to the high frequency of TP53 alterations. Therefore, ALL with low hypodiploidy is characterized by a typical pattern of chromosome losses and a remarkably high TP53 mutation frequency. Our data suggest the introduction of a novel WHO entity within the B lymphoblastic leukemia/lymphoma group showing low hypodiploid/very low tetraploid karyotype and concomitant TP53 mutation. © 2014 Wiley Periodicals, Inc.